SOSIALISASI ADAPTASI KESEHATAN BERBASIS LOKAL MENUJU TATANAN BARU DI KECAMATAN SULABESI BARAT KABUPATEN KEPULAUAN SULA - Mike Jurnida Rolobessy; Stenly Ferdinandus; Ihsan Hataul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Universitas Pattimura, 2021)
This activity identifies and analyzes the ability of health services with special qualifications for covid and non-covid, increases the knowledge and skills of the community in anticipating the spread and transmission of the Corona Virus and enforces a locally-based Health protocol in the West Sulabesi sub-district, Sula Islands Regency. The method used in the implementation of this service is through counseling about community strengthening in implementing Health Adaptation towards the new order in the Sula Islands Regency and Focus Group Discussion (FGD) is carried out in the form of brainstorming about local ideas that can be used as learning materials towards a new order in Indonesia. Sula Islands district. The process of implementing activities. The process of implementing activities begins with 1). Approaching with partners, namely the Sula Island District Health Office, the Head of the Kabau Health Center, the Kabau Village Head and the community. 2). Identifying potential partners and problems, 3). Develop counseling instruments and FGDs, 4. Conduct FGDs and Counseling on Local Based Health Adaptation Towards a New Order in West Sulabesi sub-district, Sula Islands Regency.